Judicial Diagnostic Failure: A Deconstruction of Disharmony as a Rationale in Employment Termination Rulings - Siddik, Mahfud (SIGn Jurnal Hukum, 2025)
Industrial relations jurisprudence in Indonesia is confronted by a critical anomaly: the normalisation of using “disharmony” as a rationale to legitimise employment termination—a legal ground not enshrined in labour legislation. This research aims to critically deconstruct the judicial diagnostic failure inherent in this practice. It conducts an in-depth analysis of the ratio decidendi of Court Decision Number 143/Pdt.Sus-PHI/2016/PN.Bdg juncto Supreme Court Decision Number 786 K/Pdt.Sus-PHI/2017 as a central case study. Employing a normative legal research method that combines statute and case approaches, this study examines the judicial logic and its underlying philosophical considerations. The research reveals that “disharmony” is not a valid legal cause; instead, it is merely a symptom of a deeper industrial conflict. The fatal judicial error lies in the failure to test the conflict’s root cause against the exhaustive list of grounds for termination stipulated in the law. Furthermore, the study deconstructs how the principle of utility is misinterpreted as a pragmatic justification for unethical behavior. This interpretation, framed by Radbruch’s theory of legal objectives, ironically sacrifices the pillars of legal certainty and justice. The findings confirm that normalizing the “disharmony” rationale sets a dangerous precedent that undermines the rule of law and the principle of worker protection. This research also offers an analytical framework for future judicial practice to prevent the recurrence of similar failures, particularly within the post-Job Creation Law legal regime.